Human activities and climate change are the main factors of amphibian extinction - Zhong Chen; Yuan-Sheng Cao; Meng-Sheng Dong; Wen-Bo Li (Global Ecology and Conservation, 2025)
Human activities and climate change directly influencing species distribution and species richness leading to approximately 41 % of the ∼ 8009 Amphibian species being threatened with extinction. In this study we used species distribution model (SDM) and integrated data on gross domestic product (GDP), human footprint index (HFI), normalized difference vegetation index (NDVI), human population density (HPD) and climate change to predict potential changes in the distributional range and richness of 43 amphibian species in Anhui Province, China. Our results showed that GDP and HFI, have a negative impact on amphibian distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of low GPD (≤0) and HFI (3−12). Change in temperature (Bio 8 and Bio10) were also significant contributors to a reduction in the range of amphibian species. Under the expected influence of climate change over the next 30–70 years, we found that highly suitable habitat for amphibians will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high amphibian diversity are expected to lose from 2 to 18 species. The findings provide crucial baseline information for understanding the effects of human activities and climate change on amphibian habitats in Anhui, and lay a theoretical foundation for future amphibian research and conservation efforts.